Meta Analisis Pengembangan Bahan Ajar Berbasis Riset pada Pembelajaran IPA dan Fisika - Fadilla, Intan; Maharani, Bahagia; Usmeldi, Usmeldi; Festiyed, Festiyed (Jurnal Penelitian Pembelajaran Fisika, 2019)
The focus of the study of this meta-analysis is the implementation of the educational science foundation in research-based teaching materials. This paper will reveal why it is important to develop research-based teaching materials viewed from the study of educational philosophy of science. This study is summarized from a number of science and physics education journals from various sources. Matters to be considered start from the abstract, contents, and conclusions of each journal. The method used is the meta-analysis method. The results show that. These results, as expected from the review of journals about teaching materials developed